Effect of double-pulsed gas metal arc welding (DP-GMAW) process variables on microstructural constituents and hardness of low carbon steel weld deposits. (January 2018) - Sen, Mainak; Mukherjee, Manidipto; Singh, Santosh Kumar; Pal, Tapan Kumar
Graphical abstract: Highlights: Low heat input, pulse and thermal pulse frequency resulted in higher inclusion formation. Acicular ferrite volume fraction increases with increase in inclusion volume fraction. Weld metal grain fineness is a function of higher inclusion and acicular ferrite. Grain coarsening of HAZ is primarily attributed to higher heat input. Micro-hardness of weld metal and CGHAZ decreases with increase in grain size. Abstract: In this study, a bead on plate welding on a low carbon steel plate at different parameter combinations in double-pulsed gas metal arc welding (DP-GMAW) process has been carried out. The effect of heat input, pulse frequency and thermal pulse frequency on solidification variables and microstructure of the weld metal have been thoroughly studied. Formation of inclusion and acicular ferrite during solidification has been calculated to observe the effect of process parameters on the microstructural constituents. Furthermore, the microhardness analysis of the weld metals has been carried out to evaluate the effect of microstructural variations on the property. Several linear and non-linear equations have also been developed to predict the responses as a function of different process variables. The results indicate that decrease in heat input, pulse frequency and thermal pulse frequency increases the volume fraction of inclusion and acicular ferrite in the weld metals. The higher volume fraction of acicular ferrite ultimately results in fine grain microstructure with the higher hardness of weld metals. On the other hand, the grain size of coarse grain heat affected zone (CGHAZ) at lower heat input was finer which ultimately increases the heat affected zone hardness.